Childhood Trauma among Mexican American Gang Members and Delinquent Youth: A Comparative Exploratory Study. (13th September 2014) - Cepeda, Alice; Valdez, Avelardo; Nowotny, Kathryn M.
Abstract : Abstract: This paper examines the association between childhood trauma and gang membership. Specifically, this study compares histories of potentially traumatic events as assessed by the Childhood Trauma Questionnaire among a street‐recruited random sample of Mexican American male gang members and a matched comparison group of delinquent youth. The gang and delinquent youth samples are then compared to normative samples of adolescent male psychiatric inpatients and male undergraduates. The findings show that gang members generally report experiencing lower levels of childhood trauma compared to those in the sample of delinquent youth. In fact, gang members' levels of childhood trauma more closely resemble those of the undergraduate sample. However, this analysis suggests that gang membership, and delinquency in general, may be associated with physical neglect. Copyright © 2014 John Wiley & Sons, Ltd. 'Gang membership, and delinquency in general, may be associated with physical neglect' Key Practitioner Messages: Childhood trauma prevalence and delinquent youth comparison groups are rare in gang research. Childhood trauma rates (emotional, physical and sexual abuse) were found to be lower among a sample of gang‐involved Mexican American males compared to non‐gang delinquent youth. Levels of physical neglect should be assessed for in youth regardless of gang membership. Future research should focus on family‐level sociocultural interventions that may be beneficial for gang‐involved youth and trauma‐informed interventions that may be particularly beneficial for delinquent youth in low‐income communities.